Moving for optimal immunity: the effect of acute high-intensity interval training on phenotype, virus specificity and chemokine receptor expression in human CD8+ T cells - Leuchte, Katharina; Luu, Thy Viet; Fresnillo Saló, Sara; Madsen, Kasper; Heide-Ottosen, Lise; Skadborg, Signe Koggersbøl; Kemming, Janine Sophie; Holmström, Morten Orebo; Chen, Hongjin; Olsen, Lars Rønn; Vinther, Anders; Andersen, Mads Hald; et al. (Frontiers in Immunology, 2026)
IntroductionPhysical activity induces rapid and selective leukocyte mobilization. Among the most responsive cell types to high-intensity exercise are CD8+ T cells, key effectors of immune defense against infected cells and cancer. However, comprehensive profiling of acute high-intensity interval training (HIIT)-induced modulation of the CD8+ T cell compartment remains lacking.MethodsWe assessed the effects of a supervised, group-based HIIT session on the CD8+ T cell compartment in 23 healthy participants. Blood was collected at baseline, immediately post-exercise (ex02), and one hour post-exercise (ex60). CD8+ T cells were analyzed for virus peptide reactivity using DNA-barcoded peptide-MHC multimer staining targeting 250 peptides. Differentiation status, chemokine receptor expression, and ligand regulation were assessed by flow cytometry and Olink proteomics, and finally, associations between individual characteristics and CD8+ T cell mobilization were analyzed.ResultsA single HIIT bout induced robust CD8+ T cell mobilization followed by substantial egress, which were consistent across fitness levels, body composition and age. Circulating virus-reactive T cells significantly increased in peripheral blood in response to exercise across virus types, including EBV-, SARS-CoV-2- and CMV-specific T cells. HIIT modulated chemokine receptor profiles, and memory subsets were reorganized, reducing terminally differentiated and CD57+, PD-1+, and CD28neg cells at ex60 post-exercise. Notably, catecholamines NE and EPI peaked post-exercise, and NE was selectively associated with CD8+ T cell mobilization.DiscussionIn conclusion, acute HIIT mobilizes functional, virus-reactive CD8+ T cells with features indicative of enhanced migratory and activation potential, supporting translational use from tumor immunology to infectious disease. The study is registered at clinicaltrials.gov (NCT05826496).